Development Of Liveworksheets Based Learning Materials in Class V Sciences Learning of Sukarejo State Elementary School - Yusnita, Nuke Safria; Sahudra, Tengku Muhammad; Mulyahati, Bunga (LPPPI Publishing, 2025)
The research aims to develop a product of teaching materials based on Liveworksheets for learning science, particularly social studies materials for grade V elementary school students. This study was conducted to evaluate the validity of the teaching materials through validation assessments from material experts, language experts, and teaching material experts, as well as to assess their practicality. The study uses the Research and Development (R&D) approach, employing the ADDIE model, which includes five phases: Analysis, Design, Development, Implementation, and Evaluation. The data collection methods include observation, interviews, documentation, and validation questionnaires for experts, along with response questionnaires for teachers and students. The validation results from material experts showed a percentage of 88% in the